Effect of Amidine Derivatives on Leishmania amazonensis Axenic Amastigotes - Canto-Cavalheiro, Marilene M; Echevarria, Aurea; de Souza, Marco A S; Cysne-Finkelstein, Léa; Torres, Milton A D; Leon, Leonor L (Arzneimittelforschung, 2000)
In a previous work, searching for new drugs with high efficiency and low toxicity, the in vitro antileishmanial activity of a series of seven amidine derivatives against Leishmania amazonensis promastigotes was reported. In order to compare the potential difference in the susceptibility between the two developmental stages of the parasite to these compounds, an analysis of the effects of these amidine derivatives on promastigotes and axenically grown amastigotes of L. amazonensis was carried out. Among the N,N’-diphenyl-4-R-benzamidine (where R = H, Cl, Br, CN, NO2, CH3 and OCH3) derivatives studied, the most active compounds in both developmental stages were those with -Br, -Cl, -NO2, and -OCH3 substituents, the non-substituted ones being the least active. However, the susceptibility to the drugs varied in these forms, being higher in promastigotes. The electronic theoretical parameters calculated by molecular modelling using the semi-empirical AM1 method showed good correlation with substituent constant (σpara, σ1 and F). The chemical structure and biological activity relationships were investigated in all compounds, although a small but significant correlation was observed. The obtained results suggest that other factors than the electronic parameters have an influence on the biological response.
Keywords: Amidines, structure-activity relationship; Leishmania amazonensis, amastigotes, promastigotes